2004
DOI: 10.1063/1.1689433
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic domain structures of focused ion beam-patterned cobalt films using scanning ion microscopy with polarization analysis

Abstract: Studies of magnetic domain distributions in patterned magnetic materials are of pivotal importance in the areas of ultra-high density magnetic recording, MRAM design and miniaturized magnetic sensor arrays. Scanning Ion Microscopy with Polarization Analysis (SIMPA) is used to perform in situ topographic and magnetic domain imaging and focused ion beam (FIB) patterning. For FIBpatterned 30nm thick Co films, it is found that rectangular Co bars of sizes between 10µm-30µm exhibit "S"-type, whereas circular shaped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
(11 reference statements)
1
7
0
Order By: Relevance
“…2(b). The value of 25% is consistent with earlier SIMPA measurements obtained at surfaces of 30 nm thin, continuous Co=Si films [21].…”
Section: Prl 97 107201 (2006) P H Y S I C a L R E V I E W L E T T E supporting
confidence: 81%
See 2 more Smart Citations
“…2(b). The value of 25% is consistent with earlier SIMPA measurements obtained at surfaces of 30 nm thin, continuous Co=Si films [21].…”
Section: Prl 97 107201 (2006) P H Y S I C a L R E V I E W L E T T E supporting
confidence: 81%
“…The electrons emitted from the sample surface are collected by using an extracting lens system, and the electron spin polarization (ESP) is measured by using a Mott polarimeter. SIMPA offers some unique advantages compared to many other magnetic imaging techniques, because of its capability to produce vectorial maps of the SM by directly measuring the spatially resolved vector orientation and magnitude of the ESP, which is directly proportional to the magnitude and orientation of the SM of the local area probed by the focused ion beam [20,21]. The inelastic mean free path of the emitted electrons amounts to only a few monolayers [22], which explains the high surface sensitivity of SIMPA.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Three types of micromagnetic structures appeared depending on the initial magnetization arrangements. Coercivity for the film with "C" and "S" states [8] of the micromagnetic structure is found to be relatively small comparing to the wire-like shaped film, and the film with vortex micromagnetic structure gives much smaller coercivity. Figure 6 shows probability for the appearance of vortex micromagnetic structure and coercivity regarding film size.…”
Section: Relationship Between Coercivity and Magnetic Domain Structurementioning
confidence: 98%
“…In this paper, using scanning ion microscopy with polarization analysis (SIMPA) [10,11], we report on detailed studies of the spatially-and spin-resolved magnitude and orientation of the magnetization of domain and domain wall structures of well-characterized, wedged BCT Fe/Mn/ BCT Fe films deposited pseudomorphically on surfaces of highly oriented, atomically flat Pd(1 0 0) substrate crystals as function of Mn spacer layer thickness. It is found that the MC strongly affects locally the detailed magnetic structure within the magnetic domains and domain walls of the top BCT Fe(1 0 0) films.…”
mentioning
confidence: 99%